Pengaruh Harga, Kualitas Produk Dan Lokasi Terhadap Minat Beli Generasi Milenial Di Pasar Tradisional Dinoyo Malang (Studi Pada Mahasiswa S1 Unisma Angkatan 2017-2018) - Mu’izzatul Maghfiroh; Nur Hidayati; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of price, product quality and location on the purchase interest of the millennial generation in the Dinoyo traditional market. This research is an explanatory research type, with a quantitative approach. The research method used is multiple regression analysis. The sample used in this study used the Maholtra formula with purposive sampling technique, namely the technique of determining the sample based on certain considerations which are considered suitable with the characteristics of the specified sample to be sampled and obtained 80 respondents.The results of this study indicate that partially there is a significant influence between price on purchase intention, product quality has a significant effect on purchase intention, and location has a significant effect on the purchase interest of millennial generation in the Dinoyo traditional market. Meanwhile, the simultaneous test results show that price, product quality and location have an effect on the buying interest of the millennial generation in the Dinoyo Malang traditional market. Keywords: Price, Product Quality, and Location and Purchase Interest.